Rubber-plastic composite retaining dam bag material as well as preparation method and application thereof
By using a combination of rubber sealing fill layer, ultra-high molecular weight polyethylene fiber layer, bonding transition layer and ultra-high molecular weight polyethylene protective layer in the rubber dam material, the problems of prone to aging, wear, impact and chemical corrosion of existing rubber dam materials are solved, and the material's aging resistance, wear, impact and chemical stability is achieved, extending service life and reducing maintenance costs.
Patent Information
- Application Number
- CN202411723495.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
Existing rubber dam materials are prone to aging, wear, impact and chemical corrosion during use, resulting in short service life and high maintenance and management costs.
A rubber-plastic composite dam bag material is used, which includes a rubber sealing fill layer, an ultra-high molecular weight polyethylene fiber layer, an adhesive transition layer and an ultra-high molecular weight polyethylene protective layer from the inside to the outside. Through the combination and treatment of these layers, the material's aging resistance, wear resistance, impact resistance and chemical stability are improved.
It effectively extends the service life of the dam bag, reduces maintenance and management costs, and improves the ability to resist silt, gravel wear and impacts of floating objects.
Smart Images

Figure CN119526851A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber water retaining dams and relates to a rubber-plastic composite water retaining dam bag material and a preparation method and application thereof. Background Art
[0002] At present, rubber dams are mainly composed of rubber, nylon canvas or high-strength steel wire mesh stress-bearing skeletons, which have many advantages. However, the rubber, fiber and other materials used are prone to aging due to adverse factors such as external factors. During the flood season, the river sediment wear and the floating objects hit and hang on the dam bags, causing local damage.
[0003] In the aging process, light and heat play a major role. The ultraviolet rays with a wavelength of less than 400um from the sun have high energy and can cause chemical reactions in polymer materials, causing molecular chains to break or cross-link. Under the influence of heat (temperature), thermal oxidation reactions in polymer materials will be accelerated, causing thermal cracking or thermal cross-linking of polymers. At the same time, chemical factors: ozone, chemical media (such as water, acid, alkali, salt, etc.), corrosive gases and other chemical gases, among which the aging effect of oxygen is the main factor.
[0004] In actual use, it is known that the aging process of rubber dams begins from the beginning of construction. After use, the aging phenomenon becomes increasingly obvious and gradually deepens. Generally, some black powdery substances (or slight powdering) begin to precipitate on the surface after 2 years of use, and tiny spider-web-like aging cracks begin to appear after 4 years of use, and black substances precipitate. As time goes by, the cracks become more serious, residual deformation occurs in the stress-bearing parts, the volume of the water-immersed parts expands, the rubber layer hardens, and the stress-bearing skeleton canvas delaminates and rots.
[0005] The aging of rubber dams develops with time. Currently, chemical and physical protective measures are often taken to extend the service life of rubber dams.
[0006] Chemical protection measures include selecting aging-resistant materials and formulas to manufacture dam bags or adding various effective anti-aging agents to the dam bag manufacturing materials.
[0007] Physical protection measures include: painting, rubber coating, oil spraying, metal plating, covering materials, anti-aging agent coating, etc. This measure is suitable for the protection of dam bags that have been used for many years and have begun to age, just like steel is rust-proofed with paint and can be used repeatedly.
[0008] During the flood season, the river channel is easily eroded and worn by sediment carried by the flood, and floating objects are caught and scratched. In winter, the water storage ice and other floating objects collide with each other, which often causes partial damage to the dam bag.
[0009] Due to the above-mentioned unfavorable factors, the service life of rubber dam bags is generally about 20 years, and their management and maintenance consume a lot of manpower and material resources.
[0010] Therefore, how to develop a rubber-plastic composite dam bag material that is resistant to aging, wear, impact, and chemically stable, can effectively extend the service life of the dam bag, and reduce maintenance and management costs, as well as its preparation method and application is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention
[0011] In view of this, the present invention provides a rubber-plastic composite water retaining dam bag material and a preparation method and application thereof.
[0012] In order to achieve the above object, the present invention adopts the following technical solution:
[0013] A rubber-plastic composite water dam bag material, comprising, from inside to outside, a rubber sealing filling layer, an ultra-high molecular weight polyethylene fiber layer, a bonding transition layer and an ultra-high molecular weight polyethylene protective layer;
[0014] The thickness of the rubber sealing filling layer is 3.2±0.2 mm, the thickness of the ultra-high molecular weight polyethylene fiber layer is 10±0.5 mm, the thickness of the bonding transition layer is 1±0.1 mm, and the thickness of the ultra-high molecular weight polyethylene protective layer is 10±0.5 mm.
[0015] The beneficial effects of the present invention are as follows: the rubber sealing filling layer prevents the intrusion of dust, water, gas, etc. or the leakage of the internal medium (generally a clean water source), thereby achieving the purposes of sealing, sound insulation, heat insulation, insulation and buffering.
[0016] The ultra-high molecular weight polyethylene fiber layer is a stress-bearing skeleton, and the rubber sealing filling layer plays the role of bonding and sealing, consolidating and protecting the stress-bearing skeleton of the dam bag; the bonding transition layer firmly combines the outer ultra-high molecular weight polyethylene protective layer with the inner rubber sealing filling layer and the ultra-high molecular weight polyethylene fiber layer. The rubber-plastic composite water-blocking dam bag material of the present invention is resistant to aging, wear and impact, and chemically stable, which can effectively extend the service life of the dam bag and reduce maintenance and management costs.
[0017] Furthermore, the ultra-high molecular weight polyethylene fiber layer is a mesh structure, the density of the warp of the ultra-high molecular weight polyethylene fiber layer is 2.8N / tex to 4N / tex, and the density of the weft of the ultra-high molecular weight polyethylene fiber is 2.8N / tex to 4N / tex.
[0018] Furthermore, the rubber sealing filling layer is made of the following raw materials in parts by weight: 70 parts of natural rubber, 30 parts of nitrile rubber, 5 parts of zinc oxide, 1.2 parts of stearic acid, 1 part of antioxidant A, 2.5 parts of insoluble sulfur, 0.7 parts of accelerator DM, 0.4 parts of accelerator M, 15 parts of carbon black, 175 parts of light calcium, 10 parts of engine oil, and 20 parts of white oil paste.
[0019] The beneficial effects of adopting the above further technical solution are as follows: sulfur is used to promote the cross-linking reaction of rubber, improve the hardness and wear resistance of the rubber, carbon black is used to accelerate the vulcanization process, reinforcing materials are used to improve the strength and wear resistance of rubber, and antioxidant A is used to improve the aging resistance of rubber.
[0020] Furthermore, the above-mentioned bonding transition layer is made of the following raw materials in parts by weight: 25 parts of chlorinated polyethylene, 10 parts of dibutyl phthalate, 20-25 parts of natural rubber, 20-25 parts of white carbon black, 3-4 parts of coupling agent Si-69, 2.5-3.5 parts of rubber adhesive RA or RH, 1.5-2.5 parts of zinc oxide, 0.5-1 part of stearic acid, 1.5-2.5 parts of antioxidant RD, 1-1.5 parts of accelerator thiourea, 1-1.5 parts of accelerator M, and 1-1.5 parts of insoluble sulfur.
[0021] The present invention also provides a method for preparing the above-mentioned rubber-plastic composite water dam bag material, comprising the following steps:
[0022] (1) Laminating the ultra-high molecular weight polyethylene protective layer and the bonding transition layer by a laminating machine to obtain a covering transition layer film;
[0023] (2) The bonding transition layer side of the obtained covering transition layer film is first roughened and cleaned, and then an ultra-high molecular weight polyethylene fiber layer and a rubber sealing filling layer are stacked in sequence, an adhesive is coated between the ultra-high molecular weight polyethylene fiber layer and the rubber sealing filling layer, and then the sheets are lapped with a lap machine to obtain the rubber-plastic composite water retaining dam bag material.
[0024] Beneficial effects of the present invention: The preparation method of the present invention is simple, easy to operate and suitable for large-scale production and application.
[0025] Furthermore, in step (1), the temperature of the sheet-combining machine rollers is 80±2° C., and the roller distance is 2±0.2 mm.
[0026] Furthermore, in step (2), the temperature of the sheet-combining machine rollers is 80±2° C., and the roller distance is 2±0.2 mm.
[0027] Furthermore, in step (2), the adhesive is an epoxy resin adhesive or a polyurethane adhesive.
[0028] Furthermore, the preparation method of the rubber sealing filling layer comprises the following steps:
[0029] (A) Weighing various raw materials according to the above rubber sealing filling layer;
[0030] (B) adding the raw materials into a mixing mill and mixing them to obtain a mixed rubber material;
[0031] (C) pressing the obtained mixed rubber material into a sheet by a tablet press to obtain a semi-finished rubber sealing filling layer;
[0032] (D) vulcanizing the obtained rubber sealing filling layer semi-finished product in a vulcanizer and cooling it to obtain the above-mentioned rubber sealing filling layer.
[0033] Furthermore, in step (B), the mixing temperature is 95±2°C and the mixing time is 5 minutes;
[0034] In step (C), the roller distance of the tablet press is 3 mm and the roller temperature is 50 ± 2 ° C;
[0035] In step (D), the vulcanization pressure is 15 MPa, the vulcanization temperature is 150° C., and the vulcanization time is 3 hours.
[0036] Furthermore, the method for preparing the bonding transition layer comprises the following steps:
[0037] (a) weighing the raw materials according to the above-mentioned bonding transition layer;
[0038] (b) adding chlorinated polyethylene and dibutyl phthalate into an internal mixer for plasticizing, then adding natural rubber for mixing, and then adding white carbon black, coupling agent Si-69, rubber adhesive RA or RH, zinc oxide, stearic acid, antioxidant, accelerator thiourea, accelerator M and insoluble sulfur for mixing;
[0039] (c) After mixing evenly, the material is discharged and unrolled using a two-roller unrolling machine to obtain the above-mentioned bonding transition layer.
[0040] Furthermore, in step (b), chlorinated polyethylene and dibutyl phthalate are added to an internal mixer for plasticization at a temperature of 95±2°C for 5 minutes; then natural rubber is added for mixing at a temperature of 95±2°C for 3 minutes; then white carbon black, coupling agent Si-69, rubber adhesive RA or RH, zinc oxide, stearic acid, antioxidant, accelerator thiourea, accelerator M and insoluble sulfur are added for mixing at a temperature of 95±2°C for 5 minutes.
[0041] In step (c), the roller temperature of the two-roller sheeting machine is 50±2° C. and the roller distance is 3 mm.
[0042] The present invention also provides the rubber-plastic composite water-blocking dam bag material or the use of the rubber-plastic composite water-blocking dam bag material in preparing water-blocking dam bags.
[0043] Beneficial effects of the invention: The invention gives full play to the advantages of ultra-high molecular weight polyethylene such as anti-aging, wear resistance, impact resistance, and extremely stable chemical properties, and can effectively extend the service life of the water dam, and at the same time can effectively improve the ability of the dam bag to resist the wear of sediment and gravel, and the impact or hanging of floating objects on the dam bag, and reduce the maintenance and repair costs during operation. The invention is suitable for river channel water storage projects and dam projects for estuary rivers to intercept seawater intrusion into inland rivers. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 It is a schematic diagram of the structure of the rubber-plastic composite water retaining dam bag material of the present invention. DETAILED DESCRIPTION
[0045] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] The physical property requirements of the ultra-high molecular weight polyethylene protective layer used in the present invention are shown in Table 1.
[0047] Table 1 Physical property requirements of ultra-high molecular weight polyethylene protective layer
[0048] Physical properties parameter Test method (reference standard) <![CDATA[Relative density (g / cm 3 )]]> 0.94-0.96 ASTMD1505 Tensile strength(MPa) 40-42 ASTMD638 Elongation(%) 350-370 ASTMD638
[0049] The physical property requirements of the ultra-high molecular weight polyethylene fiber used in the present invention are shown in Table 2.
[0050] Table 2 Physical property requirements of ultra-high molecular weight polyethylene protective fiber
[0051] Physical properties parameter Test method (reference standard) <![CDATA[Relative density (g / cm 3 )]]> 0.95-0.97 ASTMD1505 Tensile strength(MPa) 40-42 ASTMD638 Elongation(%) 350-370 ASTMD638
[0052] The physical property requirements of the natural rubber and nitrile rubber used as raw materials in the present invention are shown in Table 3.
[0053] Table 3 Physical property requirements of natural rubber and nitrile rubber
[0054]
[0055] The physical properties of the ultra-high molecular weight polyethylene protective layer used in the embodiment of the present invention are shown in Table 4.
[0056] Table 4 Physical properties of ultra-high molecular weight polyethylene protective layer
[0057]
[0058] The physical properties of the ultra-high molecular weight polyethylene fiber used in the embodiments of the present invention are shown in Table 5.
[0059] Table 5 Physical properties of ultra-high molecular weight polyethylene protective fibers
[0060]
[0061] The physical properties of the natural rubber and nitrile rubber used as raw materials in the examples of the present invention are shown in Table 6.
[0062] Table 6 Physical property requirements of natural rubber and nitrile rubber
[0063]
[0064] Example 1
[0065] The preparation method of the rubber-plastic composite water dam bag material comprises the following steps:
[0066] (I) A method for preparing a rubber sealing filling layer comprises the following steps:
[0067] (A) Weigh 70 kg of natural rubber, 30 kg of nitrile rubber, 5 kg of zinc oxide, 1.2 kg of stearic acid, 1 kg of antioxidant A, 2.5 kg of insoluble sulfur, 0.7 kg of accelerator DM, 0.4 kg of accelerator M, 15 kg of carbon black, 175 kg of light calcium, 10 kg of engine oil, and 20 kg of white oil paste;
[0068] (B) adding the raw materials into a mixer and mixing them at a mixing temperature of 95° C. for 5 minutes to obtain a mixed rubber material;
[0069] (C) pressing the obtained mixed rubber material into a sheet by a tablet press, the tablet press roller distance is 3 mm, the roller temperature is 50° C., and a semi-finished rubber sealing filling layer is obtained;
[0070] (D) The obtained rubber sealing filling layer semi-finished product is vulcanized in a vulcanizer at a vulcanizing pressure of 15 MPa, a vulcanizing temperature of 150° C., and a vulcanizing time of 3 hours, and then cooled to obtain a rubber sealing filling layer.
[0071] (II) A method for preparing a bonding transition layer comprises the following steps:
[0072] (a) Weigh 25 kg of chlorinated polyethylene, 10 kg of dibutyl phthalate, 25 kg of natural rubber, 25 kg of white carbon black, 3.5 kg of coupling agent Si-69, 3 kg of rubber adhesive RA, 2 kg of zinc oxide, 0.8 kg of stearic acid, 1.5 kg of antioxidant RD, 1.5 kg of accelerator thiourea, 1.5 kg of accelerator M, and 1.5 kg of insoluble sulfur;
[0073] (b) adding chlorinated polyethylene and dibutyl phthalate into an internal mixer for plasticizing at a temperature of 95.3° C. for 5 minutes, then adding natural rubber for mixing at a temperature of 95° C. for 3 minutes, then adding white carbon black, coupling agent Si-69, rubber adhesive RA, zinc oxide, stearic acid, antioxidant RD, accelerator thiourea, accelerator M and insoluble sulfur for mixing at a temperature of 94.8° C. for 5 minutes;
[0074] (c) After mixing evenly, the material is discharged and unrolled using a two-roller unroller with a roller temperature of 50° C. and a roller distance of 3 mm to obtain a bonding transition layer.
[0075] (iii) laminating the ultra-high molecular weight polyethylene protective layer and the bonding transition layer by a laminating machine, wherein the laminating machine roller temperature is 80° C. and the roller distance is 2 mm, to obtain a covering transition layer film;
[0076] (iv) The bonding transition layer side of the obtained covering transition layer film is first roughened and cleaned until the surface is not smooth, and then the ultra-high molecular weight polyethylene fiber layer and the rubber sealing filling layer are stacked in sequence and lapped with a laminating machine, 8090 epoxy resin adhesive is coated between the ultra-high molecular weight polyethylene fiber layer and the rubber sealing filling layer, the laminating machine roller temperature is 80°C, the roller distance is 2mm, and the rubber-plastic composite water dam bag material is obtained.
[0077] The rubber-plastic composite water-blocking dam bag material includes, from the inside to the outside, a rubber sealing filling layer, an ultra-high molecular weight polyethylene fiber layer, a bonding transition layer and an ultra-high molecular weight polyethylene protective layer;
[0078] The thickness of the rubber sealing filling layer is 3.3 mm, the thickness of the ultra-high molecular weight polyethylene fiber layer is 10 mm, the thickness of the bonding transition layer is 1 mm, and the thickness of the ultra-high molecular weight polyethylene protective layer is 10 mm.
[0079] The ultra-high molecular weight polyethylene fiber layer is a mesh structure, the density of the warp of the ultra-high molecular weight polyethylene fiber layer is 2.8 N / tex, and the density of the weft of the ultra-high molecular weight polyethylene fiber is 2.8 N / tex.
[0080] Example 2
[0081] The preparation method of the rubber-plastic composite water dam bag material comprises the following steps:
[0082] (I) A method for preparing a rubber sealing filling layer comprises the following steps:
[0083] (A) Weigh 70 kg of natural rubber, 30 kg of nitrile rubber, 5 kg of zinc oxide, 1.2 kg of stearic acid, 1 kg of antioxidant A, 2.5 kg of insoluble sulfur, 0.7 kg of accelerator DM, 0.4 kg of accelerator M, 15 kg of carbon black, 175 kg of light calcium, 10 kg of engine oil, and 20 kg of white oil paste;
[0084] (B) adding the raw materials into a mixer and mixing them at a mixing temperature of 95° C. for 5 minutes to obtain a mixed rubber material;
[0085] (C) pressing the obtained mixed rubber material into a sheet by a tablet press, the tablet press roller distance is 3 mm, the roller temperature is 50° C., and a semi-finished rubber sealing filling layer is obtained;
[0086] (D) The obtained rubber sealing filling layer semi-finished product is vulcanized in a vulcanizer at a vulcanizing pressure of 15 MPa, a vulcanizing temperature of 150° C., and a vulcanizing time of 3 hours, and then cooled to obtain a rubber sealing filling layer.
[0087] (II) A method for preparing a bonding transition layer comprises the following steps:
[0088] (a) Weigh 25 kg of chlorinated polyethylene, 10 kg of dibutyl phthalate, 20-25 kg of natural rubber, 22 kg of white carbon black, 3.6 kg of coupling agent Si-69, 3 kg of rubber adhesive RA, 2.1 kg of zinc oxide, 0.75 kg of stearic acid, 1.8 kg of antioxidant RD, 1.2 kg of accelerator thiourea, 1.2 kg of accelerator M, and 1 kg of insoluble sulfur;
[0089] (b) adding chlorinated polyethylene and dibutyl phthalate into an internal mixer for plasticizing at a temperature of 96° C. for 5 minutes, then adding natural rubber for mixing at a temperature of 95° C. for 3 minutes, then adding white carbon black, coupling agent Si-69, rubber adhesive RA, zinc oxide, stearic acid, antioxidant RD, accelerator thiourea, accelerator M and insoluble sulfur for mixing at a temperature of 95° C. for 5 minutes;
[0090] (c) After mixing evenly, the material is discharged and unrolled using a two-roller unroller with a roller temperature of 50.5° C. and a roller distance of 3 mm to obtain a bonding transition layer.
[0091] (iii) laminating the ultra-high molecular weight polyethylene protective layer and the bonding transition layer by a laminating machine, wherein the laminating machine roller temperature is 80° C. and the roller distance is 2 mm, to obtain a covering transition layer film;
[0092] (iv) The bonding transition layer side of the obtained covering transition layer film is first roughened and cleaned until the surface is not smooth, and then the ultra-high molecular weight polyethylene fiber layer and the rubber sealing filling layer are stacked in sequence and lapped with a laminating machine. 8090 epoxy resin adhesive is coated between the ultra-high molecular weight polyethylene fiber layer and the rubber sealing filling layer. The laminating machine roller temperature is 80°C and the roller distance is 2mm to obtain a rubber-plastic composite water dam bag material.
[0093] The rubber-plastic composite water-blocking dam bag material includes, from the inside to the outside, a rubber sealing filling layer, an ultra-high molecular weight polyethylene fiber layer, a bonding transition layer and an ultra-high molecular weight polyethylene protective layer;
[0094] The thickness of the rubber sealing filling layer is 3.2 mm, the thickness of the ultra-high molecular weight polyethylene fiber layer is 10.2 mm, the thickness of the bonding transition layer is 1 mm, and the thickness of the ultra-high molecular weight polyethylene protective layer is 10.2 mm.
[0095] The ultra-high molecular weight polyethylene fiber layer is a mesh structure, the density of the warp of the ultra-high molecular weight polyethylene fiber layer is 3N / tex, and the density of the weft of the ultra-high molecular weight polyethylene fiber is 3N / tex.
[0096] Example 3
[0097] The preparation method of the rubber-plastic composite water dam bag material comprises the following steps:
[0098] (I) A method for preparing a rubber sealing filling layer comprises the following steps:
[0099] (A) Weigh 70 kg of natural rubber, 30 kg of nitrile rubber, 5 kg of zinc oxide, 1.2 kg of stearic acid, 1 kg of antioxidant A, 2.5 kg of insoluble sulfur, 0.7 kg of accelerator DM, 0.4 kg of accelerator M, 15 kg of carbon black, 175 kg of light calcium, 10 kg of engine oil, and 20 kg of white oil paste;
[0100] (B) adding the raw materials into a mixer and mixing them at a mixing temperature of 95° C. for 5 minutes to obtain a mixed rubber material;
[0101] (C) pressing the obtained mixed rubber material into a sheet by a tablet press, the tablet press roller distance is 3 mm, the roller temperature is 50° C., and a semi-finished rubber sealing filling layer is obtained;
[0102] (D) The obtained rubber sealing filling layer semi-finished product is vulcanized in a vulcanizer at a vulcanizing pressure of 15 MPa, a vulcanizing temperature of 150° C., and a vulcanizing time of 3 hours, and then cooled to obtain a rubber sealing filling layer.
[0103] (II) A method for preparing a bonding transition layer comprises the following steps:
[0104] (a) Weigh 25 kg of chlorinated polyethylene, 10 kg of dibutyl phthalate, 25 kg of natural rubber, 25 kg of white carbon black, 4 kg of coupling agent Si-69, 3.5 kg of rubber adhesive RA, 2.5 kg of zinc oxide, 1 kg of stearic acid, 2.5 kg of antioxidant RD, 1.5 kg of accelerator thiourea, 1.5 kg of accelerator M, and 1.5 kg of insoluble sulfur;
[0105] (b) adding chlorinated polyethylene and dibutyl phthalate into an internal mixer for plasticizing at a temperature of 94° C. for 5 minutes, then adding natural rubber for mixing at a temperature of 94° C. for 3 minutes, then adding white carbon black, coupling agent Si-69, rubber adhesive RA, zinc oxide, stearic acid, antioxidant RD, accelerator thiourea, accelerator M and insoluble sulfur for mixing at a temperature of 94° C. for 5 minutes;
[0106] (c) After mixing evenly, the material is discharged and unrolled using a two-roller unroller with a roller temperature of 50° C. and a roller distance of 3 mm to obtain a bonding transition layer.
[0107] (iii) laminating the ultra-high molecular weight polyethylene protective layer and the bonding transition layer by a laminating machine, with the laminating machine roller temperature being 79.5° C. and the roller distance being 2.1 mm, to obtain a covering transition layer film;
[0108] (IV) The bonding transition layer side of the obtained covering transition layer film is first roughened and cleaned until the surface is not smooth, and then the ultra-high molecular weight polyethylene fiber layer and the rubber sealing filling layer are stacked in sequence and lapped with a laminating machine. 8090 epoxy resin adhesive is coated between the ultra-high molecular weight polyethylene fiber layer and the rubber sealing filling layer. The laminating machine roller temperature is 79.5°C and the roller distance is 2.1mm to obtain a rubber-plastic composite water retaining dam bag material.
[0109] The rubber-plastic composite water-blocking dam bag material includes, from the inside to the outside, a rubber sealing filling layer, an ultra-high molecular weight polyethylene fiber layer, a bonding transition layer and an ultra-high molecular weight polyethylene protective layer;
[0110] The thickness of the rubber sealing filling layer is 3.15 mm, the thickness of the ultra-high molecular weight polyethylene fiber layer is 9.8 mm, the thickness of the bonding transition layer is 0.9 mm, and the thickness of the ultra-high molecular weight polyethylene protective layer is 9.8 mm.
[0111] The ultra-high molecular weight polyethylene fiber layer is a mesh structure, the density of the warp of the ultra-high molecular weight polyethylene fiber layer is 3N / tex, and the density of the weft of the ultra-high molecular weight polyethylene fiber is 3N / tex.
[0112] The disclosed embodiments are described to enable one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A rubber-plastic composite dam bag material, characterized in that: From inside to outside, it includes: a rubber sealing filling layer, an ultra-high molecular weight polyethylene fiber layer, a bonding transition layer and an ultra-high molecular weight polyethylene protective layer; The thickness of the rubber sealing filling layer is 3.2±0.2 mm, the thickness of the ultra-high molecular weight polyethylene fiber layer is 10±0.5 mm, the thickness of the bonding transition layer is 1±0.1 mm, and the thickness of the ultra-high molecular weight polyethylene protective layer is 10±0.5 mm.
2. The rubber-plastic composite water dam bag material according to claim 1, characterized in that: The ultra-high molecular weight polyethylene fiber layer is a mesh structure, the density of the warp of the ultra-high molecular weight polyethylene fiber layer is 2.8N / tex to 4N / tex, and the density of the weft of the ultra-high molecular weight polyethylene fiber is 2.8N / tex to 4N / tex.
3. The rubber-plastic composite water dam bag material according to claim 1, characterized in that: The rubber sealing filling layer is made of the following raw materials in parts by weight: 70 parts of natural rubber, 30 parts of nitrile rubber, 5 parts of zinc oxide, 1.2 parts of stearic acid, 1 part of antioxidant A, 2.5 parts of insoluble sulfur, 0.7 parts of accelerator DM, 0.4 parts of accelerator M, 15 parts of carbon black, 175 parts of light calcium, 10 parts of engine oil, and 20 parts of white oil paste.
4. The rubber-plastic composite water dam bag material according to claim 1, characterized in that: The bonding transition layer is prepared from the following raw materials in parts by weight: 25 parts of chlorinated polyethylene, 10 parts of dibutyl phthalate, 20-25 parts of natural rubber, 20-25 parts of white carbon black, 3-4 parts of coupling agent Si-69, 2.5-3.5 parts of rubber adhesive RA or RH, 1.5-2.5 parts of zinc oxide, 0.5-1 part of stearic acid, 1.5-2.5 parts of antioxidant RD, 1-1.5 parts of accelerator thiourea, 1-1.5 parts of accelerator M, and 1-1.5 parts of insoluble sulfur.
5. A method for preparing the rubber-plastic composite water dam bag material according to any one of claims 1 to 4, characterized in that: The steps include: (1) Laminating the ultra-high molecular weight polyethylene protective layer and the bonding transition layer by a laminating machine to obtain a covering transition layer film; (2) The bonding transition layer side of the obtained covering transition layer film is first roughened and cleaned, and then an ultra-high molecular weight polyethylene fiber layer and a rubber sealing filling layer are stacked in sequence, an adhesive is coated between the ultra-high molecular weight polyethylene fiber layer and the rubber sealing filling layer, and then the sheets are lapped with a lap machine to obtain the rubber-plastic composite water retaining dam bag material.
6. The method for preparing a rubber-plastic composite water dam bag material according to claim 5, characterized in that: In step (1), the temperature of the sheet-combining machine rollers is 80±2° C., and the roller distance is 2±0.2 mm.
7. The method for preparing a rubber-plastic composite water dam bag material according to claim 5, characterized in that: In step (2), the temperature of the sheet-combining machine rollers is 80±2° C., and the roller distance is 2±0.2 mm.
8. The method for preparing a rubber-plastic composite water dam bag material according to claim 5, characterized in that: The method for preparing the rubber sealing filling layer comprises the following steps: (A) Weighing the raw materials for the rubber sealing filling layer according to claim 3; (B) adding the raw materials into a mixing mill and mixing them to obtain a mixed rubber material; (C) pressing the obtained mixed rubber material into a sheet by a tablet press to obtain a semi-finished rubber sealing filling layer; (D) vulcanizing the obtained rubber sealing filling layer semi-finished product in a vulcanizer, and cooling it to obtain the rubber sealing filling layer.
9. The method for preparing a rubber-plastic composite water dam bag material according to claim 5, characterized in that: The method for preparing the bonding transition layer comprises the following steps: (a) weighing the raw materials for the bonding transition layer according to claim 4; (b) adding chlorinated polyethylene and dibutyl phthalate into an internal mixer for plasticizing, then adding natural rubber for mixing, and then adding white carbon black, coupling agent Si-69, rubber adhesive RA or RH, zinc oxide, stearic acid, antioxidant, accelerator thiourea, accelerator M and insoluble sulfur for mixing; (c) After the mixing is uniform, the material is discharged and sheeted using a two-roll sheeting machine to obtain the bonding transition layer.
10. Use of the rubber-plastic composite water-retaining dam bag material according to any one of claims 1 to 4 or the rubber-plastic composite water-retaining dam bag material according to any one of claims 5 to 9 in the preparation of water-retaining dam bags.
Citation Information
Patent Citations
Colorful chlorinated polyethylene rubber dam bag and production process thereof
CN105881925A
Colored oil-resistance and flame-retardation chlorinated polyethylene conveyer belt and manufacturing method thereof
CN106084510A
Method for preparing ultra-high molecular weight polyethylene rubber composite material
CN107459680A
Outer-layer rubber for rubber dam and preparation method of outer-layer rubber
CN117777568A
Rubber dam bag
CN203247540U
Cited By
An Integrated Rubber Plate For Rubber Dam And Rubber Dam Using It
KR103014070B1